2018
DOI: 10.5853/jos.2018.01788
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Guides on Stroke Thrombolysis for Anticoagulated Patients from Japan: Application to Other Populations

Abstract: Development of direct oral anticoagulants and their antidotes has led to the need to reconsider the eligibility of acute stroke patients who have been taking oral anticoagulants for intravenous thrombolysis. Officially authorized Japanese guidelines on this issue were revised twice at the time of approval for clinical use of direct oral anticoagulants and idarucizumab, a specific reversal agent for dabigatran. A unique recommendation in the latest Japanese clinical guides was that thrombolysis can be recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Several case reports suggest that thrombolysis and thrombectomy can be performed safely after dabigatran reversal with idarucizumab [22,23]. Although these data are limited, recommendations have been published regarding acute reperfusion therapy with idarucizumab for patients with ischemic stroke receiving dabigatran [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports suggest that thrombolysis and thrombectomy can be performed safely after dabigatran reversal with idarucizumab [22,23]. Although these data are limited, recommendations have been published regarding acute reperfusion therapy with idarucizumab for patients with ischemic stroke receiving dabigatran [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Antiplatelet prescription did not affect group assignment. For the sensitivity analysis, we further defined confirmed therapeutic OAC as specific drug activity > 50 ng/ml in patients taking DOAC [11][12][13][14][15] and INR > 1.7 in VKA patients. If no specific drug activity was available in patients taking DOAC, confirmed therapeutic OAC was defined as reported previously [16].…”
Section: Methodsmentioning
confidence: 99%
“…The above-mentioned nationwide questionnaire revealed that asymptomatic intracranial hemorrhage occurred in eight of 13 patients when IV thrombolysis or endovascular therapy was performed within 4 h after the last dosing of DOAC, suggesting that the incidence was higher than treatment beyond 4 h performed in four of 39 patients, and the potential risks were posed to provide IV thrombolysis early after the last dosing. 57) A single-center study also demonstrated that intracranial hemorrhage occurred in three of 11 patients treated with IV thrombolysis within 6 h after the last dosing of DOACs and in one of 11 patients receiving treatment beyond 6 h. 56) The third edition recommended that patients should be ineligible for IV thrombolysis if it is confirmed that thrombolysis is performed within 4 h of the last dose of DOACs, regardless of coagulation marker levels.…”
Section: General Eligibility For IV Thrombolysis In Patients Treated mentioning
confidence: 99%
“…Of 48 reported patients treated with dabigatran who received IV thrombolysis followed by idarucizumab until February 2018, 30 were considered to show improvement in the mRS score of 0–2, and 3 were dead. 56) In Europe, where was reported in 35 of 48 patients, a growing body of clinical guides based on the expert opinion were published to recommend IV thrombolysis followed by idarucizumab. 58,59) The Consensus Guides on Stroke Thrombolysis and Thrombectomy for Anticoagulated Patients indicated detailed recommendations on acute reperfusion therapy in patients treated with dabigatran taking account of preceding guides from Europe and eligibility criteria on coagulation markers in Japan (Fig.…”
Section: Eligibility For IV Thrombolysis In Patients Treated With Dabmentioning
confidence: 99%
See 1 more Smart Citation